2018
DOI: 10.4067/s0717-95022018000300979
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Activity of Extract and Active Fraction of Turbinaria decurrens Bory on Colon Cancer Cell Line HCT-116

Abstract: Turbinaria deccurrens Bory contains bioactive compound that is beneficial for health. Turbinaria deccurrens Bory is one of many species of brown seaweed that grows in Indonesian marine life and has been known to have cytotoxic activity. The aim of this study is to determine fucoxantin content and the cytotoxic activity of extract and fraction T. decurrens on colon cancer cell lines. Cytotoxic assay of ethanolic extract, n-hexane, ethyl acetate and ethanolic fractions against HCT-116 by MTS assay using Cell Cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…The methanolic extracts of A. platensis showed varying degrees of inhibitory efficacy against the four evaluated human tumor cell lines. This agreed with Mashjoor et al [ 35 ], Hernandez et al [ 36 ] and Deviyani et al [ 37 ] who reported cytotoxic potential and activity of the A. platensis extracts against three cell lines, including MCF7, HeLa and HepG2.…”
Section: Discussionsupporting
confidence: 91%
“…The methanolic extracts of A. platensis showed varying degrees of inhibitory efficacy against the four evaluated human tumor cell lines. This agreed with Mashjoor et al [ 35 ], Hernandez et al [ 36 ] and Deviyani et al [ 37 ] who reported cytotoxic potential and activity of the A. platensis extracts against three cell lines, including MCF7, HeLa and HepG2.…”
Section: Discussionsupporting
confidence: 91%
“…The chemical constituents of the crude extracts of the tested seaweeds were analyzed using GC-MS, and the identi ed compounds with their molecular formula, peak area, and the chemical group were presented in Tables 4-8 Indonesia were 1.512 µg mL − 1 , and 3.058 µg mL − 1 , respectively. Differences in cytotoxic effect may be due to differences in seaweed species, collection site, extraction solvent, and assay methods (Zakaria et al, 2018).…”
Section: Gc-ms Analysismentioning
confidence: 99%
“…Previous studies revealed several mechanisms of seaweed extracts that exert anticancer effects (Farooqi et al, 2012;Chantree et al, 2021). In CRC, there is evidence suggesting the anticancer activities of seaweed (Alves et al, 2018;Deviyani-Zakaria et al, 2018;Al-Aadily et al, 2022). Interestingly, there was a low risk of CRC development in East Asian people who usually consumed seaweed (Cotas et al, 2021).…”
Section: Introductionmentioning
confidence: 99%